Mnemonik : Solusi Kreatif untuk Meningkatkan Kemampuan Menghafal Kosa Kata Bahasa Arab Siswi Madrasah Aliyah Nurul Jadid - Sulton Firdaus; Siti Hafidah (LP2M STIT Palapa Nusantara, 2020)
This study aims to determine the process of learning Arabic vocabulary with several methods in the class, and how teachers deal with these obstacles. There needs to be a breakthrough for teachers to be more creative in choosing alternative methods, the methods used by teachersin Madrasah Aliyah Nurul Jadid to make it easier for students to improve their memory in memorizing Arabic vocabulary. In its application is to use mnemonic techniques including those that are often used, namely association and rhyme. This research is a descriptive study with a qualitative approach, data collection techniques that researchers do by observation and interviews, the results of this study indicate: First, the application of Arabic vocabulary learning using the association and rhyme method runs well and smoothly, the learning process becoms more fun, can foster student enthusiasm, thus it can be concluded that the teaching of vocabulary using these methods proved effective for improving student learning outcomes Madrasah Aliyah Nurul Jadid.